2014
DOI: 10.4310/jdg/1393424917
|View full text |Cite
|
Sign up to set email alerts
|

Interior curvature estimates and the asymptotic plateau problem in hyperbolic space

Abstract: Abstract. We show that for a very general class of curvature functions defined in the positive cone, the problem of finding a complete strictly locally convex hypersurface in H n+1 satisfying f (κ) = σ ∈ (0, 1) with a prescribed asymptotic boundary Γ at infinity has at least one smooth solution with uniformly bounded hyperbolic principal curvatures. Moreover if Γ is (Euclidean) starshaped, the solution is unique and also (Euclidean) starshaped while if Γ is mean convex the solution is unique. We also show via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…In this section, we shall focus on prescribed Gauss curvature equation, that is, equation (1.1) with k = n. Before we discuss this type of equation, we first present some preliminary formulae on vertical graph of u, which can be found in [7,5,6,8,12,13]. The counterparts in Euclidean space can be found in [2].…”
Section: Prescribed Gauss Curvature Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we shall focus on prescribed Gauss curvature equation, that is, equation (1.1) with k = n. Before we discuss this type of equation, we first present some preliminary formulae on vertical graph of u, which can be found in [7,5,6,8,12,13]. The counterparts in Euclidean space can be found in [2].…”
Section: Prescribed Gauss Curvature Equationsmentioning
confidence: 99%
“…Asymptotic Plateau type problem (1.1) is usually more difficult than common Dirichlet problems due to the singularity at Γ. When ψ = σ ∈ (0, 1) is a prescribed constant, Guan, Spruck, Szapiel and Xiao [4,7,5,6,8] studied problem (1.1) thoroughly by analyzing the approximating Dirichlet problem…”
Section: Introductionmentioning
confidence: 99%
“…First, we shall present some preliminary knowledge which may be found in [10,8,9,11,21]. The coordinate vector fields on vertical graph of u are given by…”
Section: Estimatementioning
confidence: 99%
“…where ǫ is a small positive constant, ψ = σ ∈ (0, 1) is a prescribed constant and f satisfies certain assumptions. Extensive study by this method can be found in [7,10,8,9,11], where the estimates for solutions to (1.2) have to be ǫ-independent in order to prove existence results for asymptotic problem (1.1). For nonconstant ψ, Szapiel [22] investigated the existence of strictly locally convex solutions to the approximating problem (1.2).…”
Section: Introductionmentioning
confidence: 99%
“…The microscopic convexity principle, with applications in geometric equations on manifolds, has been established in [2] for the very general fully nonlinear elliptic and parabolic operators of second order. Guan, Spruck and Xiao [9] point out that the asymptotic Plateau problem for finding a complete strictly locally convex hypersurface is reduced to the Dirichlet problem for a fully nonlinear equation, a special form of which is the k−Hessian equation, see Corollary 1.11, [9] and they have proved the existence of such hypersurface, it is especially interesting that they have proved that, if ∂Ω is strictly (Euclidean) star-shaped about the origin, so is the unique solution, see Theorem 1.5, [9]. For the k-Hessian equation with k = 2, n = 3, the power convexity for Dirichlet problem of equation (1.1) with f = 1, and log-convexity for the eigenvalue problem have been studied in [16,17], see also [18].…”
Section: Introductionmentioning
confidence: 99%